RESILIENCE OF PARENTS DIAGNOSED WITH MENTAL HEALTH DISORDERS IN ADAPTIVE CHILDCARE - Widia, Amanda Putri; Hidayati, Sri (International Journal of Multidisciplinary Reseach, 2025)
This study aims to understand the phenomenon of resilience in parents diagnosed with Mental Health Disorders (GKM) in the context of adaptive childcare. Using a qualitative phenomenological approach, this study explored the subjective experiences of two participants (married couples) who both lived with GKM and had children. The results of in-depth interviews showed that although the diagnosis of GKM brought significant emotional and relational challenges, participants demonstrated strong resilience. This resilience is manifested through the discovery of meaning in the role of parents as a reminder to keep struggling, as well as the utilization of adaptive parenting strategies such as flexible task sharing and external support from spouses, family psychologists, and the community. The findings indicate that GKM does not necessarily hinder adaptive parenting capacity, but rather encourages unique resilience mechanisms. This research contributes to the literature by presenting a strengths-based perspective, highlighting the adaptive capacity of parents with GKM, and providing practical implications for developing more targeted psychosocial support interventions.